Predicting poor postoperative acute pain outcome in adults: an international, multicentre database analysis of risk factors in 50, 005 patients. (27th July 2020) - Schnabel, Alexander; Yahiaoui-Doktor, Maryam; Meissner, Winfried; Zahn, Peter Konrad; Pogatzki-Zahn, Esther Miriam
Abstract : Supplemental Digital Content is Available in the Text. Eight risk factors were identified in a large international database. Patients with 3 or more risk factors are at higher risk for poor pain outcome. Abstract: Background: The aim of this study was to determine simple risk factors for severe pain intensity (≥7 points on a numeric rating scale [NRS]), to analyse their relation to other patient-reported outcome measures and to develop a simple prediction model. Methods: We used data from 50, 005 patients from the PAIN-OUT project. Within a first data set (n = 33, 667), relevant risk factors were identified by logistic binary regression analysis, assessed for additional patient-reported outcome measures beyond pain intensity and summed up for developing a simple risk score. Finally, sum of factors was plotted against postoperative pain outcomes within a validation data set (n = 16, 338). Results: Odds ratios (OR) for the following risk factors were identified: younger age (<54 years, OR: 1.277), preoperative chronic pain at the site of surgery (OR: 1.195), female sex (OR: 1.433), duration of surgery (>90 minutes, OR: 1.308), preoperative opioid intake (OR: 1.250), feeling anxious (OR: 1.239) and feeling helpless due to pain (OR: 1.198), and the country of the recruiting centre (OR: 1.919). Patients with ≥3 risk factors had more severe pain intensity scores, spent a longer time in severe pain, and wished to have received more pain treatment ( P < 0.001). A simple risk score was created with 4 risk factors showing a moderate prediction level. Conclusions: Patients with ≥3 risk factors are at higher risk for poor postoperative acute pain outcome after surgery. Future studies using this score might show that preventive strategies might decrease pain intensity, pain-related postoperative dysfunction, and the development of chronic pain.